2018
DOI: 10.3389/fpsyt.2018.00332
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Endoplasmic Reticulum Stress Induced by Repeated Short-Term Sevoflurane Exposure in Early Life of Rats

Abstract: Sevoflurane is one of the most commonly used volatile anaesthetics for children, but the safety of prolonged or repeated clinical use of sevoflurane in infants or children is controversial. Here, we investigated the effects of sevoflurane on rats in early life and the time scale of those effects. Our behavioral results indicated that repeated short-term exposure of new-born rats to sevoflurane caused learning and memory impairment, while a single exposure of rats to sevoflurane was relatively safe. Further mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Furthermore, excessive stimulation impairs calcium homeostasis in the neurons, thus affecting the normal functioning of ER and results in the accumulation of the misfolded proteins (Bhardwaj et al, 2017;Prentice et al, 2015). Thus, this study was an attempt to further association Shen et al, 2018). Since overstimulation of neurons and glutamate receptors in the central nervous system (CNS) plays a key role in the learning and memory of the animals (Huo et al, 2015), therefore motor and memory impairments are believed to be get affected following ER stress (Shen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, excessive stimulation impairs calcium homeostasis in the neurons, thus affecting the normal functioning of ER and results in the accumulation of the misfolded proteins (Bhardwaj et al, 2017;Prentice et al, 2015). Thus, this study was an attempt to further association Shen et al, 2018). Since overstimulation of neurons and glutamate receptors in the central nervous system (CNS) plays a key role in the learning and memory of the animals (Huo et al, 2015), therefore motor and memory impairments are believed to be get affected following ER stress (Shen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study was an attempt to further association Shen et al, 2018). Since overstimulation of neurons and glutamate receptors in the central nervous system (CNS) plays a key role in the learning and memory of the animals (Huo et al, 2015), therefore motor and memory impairments are believed to be get affected following ER stress (Shen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the UPR may represent one of the most important cellular adaptive mechanisms to injury. We were the first to report that fetal exposure to inhalational anesthetics causes ER stress and neuronal cell death [34]; since then, several other papers have confirmed that general anesthesia causes ER stress [75][76][77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…have shown that repeated exposure to sevoflurane during pregnancy inhibits neuronal migration and leads to defective neuronal migration in offspring, suggesting that sevoflurane affects the brain development (Chai, 2019). Sevoflurane can also induce neuronal apoptosis in newborn mice or rats and cause cognitive dysfunction by activating the endoplasmic reticulum stress pathway (Liu et al., 2017; Shen, 2018). In addition to the endoplasmic reticulum, mitochondria also play an important role in the regulation of apoptosis.…”
Section: Sevoflurane Neuroapoptosis and Neuroinflammationmentioning
confidence: 99%